Sorptivity of self-compacting concrete containing fly ash and silica fume - Leung, H. Y.; Kim, J.; Nadeem, A.; Jaganathan, Jayaprakash; Anwar, M. P. (Construction and Building Materials, 2016)
This paper presents the surface water absorption of self-compacting concrete (SCC) containing fly ash and silica fume using sorptivity test. Ordinary Portland cement was partially replaced by various combinations of fly ash and silica fume. Test results show that the presence of fly ash and silica fume significantly reduce the surface water absorption of self-compacting concrete at a water-binder ratio of 0.38. When only fly ash is used to partially replace Ordinary Portland cement, a more noticeable reduction in sorptivity is found when the fly ash content is greater than 20%.
Keywords: Compressive strength; Fly ash; Self-compacting concrete; Silica fume; Sorptivity; Water absorption